2021
DOI: 10.1007/s00415-021-10717-0
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of N-acetyl-l-leucine in Niemann–Pick disease type C

Abstract: Objective To investigate the safety and efficacy of N-acetyl-l-leucine (NALL) on symptoms, functioning, and quality of life in pediatric (≥ 6 years) and adult Niemann–Pick disease type C (NPC) patients. Methods In this multi-national, open-label, rater-blinded Phase II study, patients were assessed during a baseline period, a 6-week treatment period (orally administered NALL 4 g/day in patients ≥ 13 years, weight-tiered doses for patients 6–12 years), and … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
30
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 33 publications
(38 citation statements)
references
References 21 publications
2
30
0
2
Order By: Relevance
“…The results of the trial are consistent with a parallel trial completed for NPC, where treatment also had a statistically significant and clinically meaningful effect on the primary CI-CS and secondary (SARA, CGI-C, etc) endpoints. 7 As briefly described, these clinical findings correlate directly with studies in the GM2 gangliosidosis mouse model (Hexb -/-) and NPC mouse model (NPC -/-) where N-acetyl-leucine reduced ataxia when treatment was commenced pre-symptomatically (from 3-weeks of age onward) or symptomatically (for 1-week treatment, starting at 8-weeks of age). NALL restored aerobic (pyruvate dihydrogenase-dependent) and enhanced anaerobic (lactate dehydrogenasedependent) glycolysis, and returned the glutamate-metabolizing enzyme, glutamate dehydrogenase, to levels observed in Hexb +/+ and NPC +/+ null mice.…”
Section: Discussionsupporting
confidence: 63%
See 3 more Smart Citations
“…The results of the trial are consistent with a parallel trial completed for NPC, where treatment also had a statistically significant and clinically meaningful effect on the primary CI-CS and secondary (SARA, CGI-C, etc) endpoints. 7 As briefly described, these clinical findings correlate directly with studies in the GM2 gangliosidosis mouse model (Hexb -/-) and NPC mouse model (NPC -/-) where N-acetyl-leucine reduced ataxia when treatment was commenced pre-symptomatically (from 3-weeks of age onward) or symptomatically (for 1-week treatment, starting at 8-weeks of age). NALL restored aerobic (pyruvate dihydrogenase-dependent) and enhanced anaerobic (lactate dehydrogenasedependent) glycolysis, and returned the glutamate-metabolizing enzyme, glutamate dehydrogenase, to levels observed in Hexb +/+ and NPC +/+ null mice.…”
Section: Discussionsupporting
confidence: 63%
“…We used the same methodology study design as the one employed in a previous study and described in detail before. 7,12 The IB1001-201 clinical trial was separated into two study phases to enable the investigation of both the symptomatic ("Parent Study"), and long-term ("Extension Phase") safety and efficacy of NALL. The results of the Parent Study are reported below.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…In patients with Niemann-Pick type C (NPC), the SARA and SCAFI scores also improved; only one patient reported transient dizziness [8]. These findings in NPC were supported by a more recent phase 2 trial [9] and preclinical studies in animal models as well as in gangliosidosis GM2 [10,11]. The third case series applying AL (500 mg, 4-3-3 tablets per day) in different types of cerebellar ataxia showed improved walking stability in 14 out of 18 patients measured on a GAITRite system [12].…”
Section: Patient Data and Study Designmentioning
confidence: 76%